Adat Basandi Syarak, Syarak Basandi Kitabullah: Understanding Local Wisdom in Social Studies Learning - Permata, Bunga Dinda (LANGGAM: International Journal of Social Science Education, Art and Culture, 2025)
This research explains the philosophy of "Adat Basandi Syarak, Syarak Basandi Kitabullah" in Social Studies learning as a learning resource within the context of Minangkabau society. Through a literature study method, this research explores the concepts, history, and practical implications of this philosophy in Social Studies education. The discussion encompasses the philosophical concepts of this philosophy that emphasize harmony between customs and religion, as well as its important role in student character formation. The results of the literature study indicate that integrating this philosophy into Social Studies education requires the development of a balanced curriculum between theoretical aspects and local cultural values. Teachers also need to be trained to integrate cultural and religious values into daily learning, while evaluation and assessment must also reflect students' understanding of these values. Furthermore, the discussion regarding the impact of integrating this philosophy on student character formation highlights the importance of learning that emphasizes attitudes of tolerance, justice, responsibility, and leadership. Thus, through a holistic approach to integrating the philosophy of "Adat Basandi Syarak, Syarak Basandi Kitabullah" in Social Studies learning, it is hoped that students can develop strong character and bring positive impact to Minangkabau society and society in general.